SYSTEM DESIGN IN STORES SUPPLY RICE RICE BY USING XYZ VISUAL FOXPRO 9.0 - Heri Kiswanto; Yudi Irawan Chandra (Jurnal Sistem Informasi, 2010)
Scientific writing is about a supply System Design Application of Rice in RiceStores XYZ. This application is made ??to simplify the data storage of rice ofrice stores XYZ. In scientific writing, the application to make the author ofRice supply system design using Microsoft Visual Foxpro 9.0 which canprovide convenience in data storage of rice, rice supply, rice stocks and securityin storing data to the user agent of rice stores.